PENGARUH PELARUT KLOROFORM DALAM PEMURNIAN GLISEROL DENGAN PROSES ASIDIFIKASI ASAM KLORIDA - Windi Monica Surbakti, Gerson Rico M.H, Mersi Suriani Sinaga (Jurnal Teknik Kimia USU, 2016)
Glycerol as a byproduct of biodiesel production was approximately formed 10% of the biodiesel weight. Impurities which contained in the glycerol such as catalyst, soap, methanol, water, salt, and matter organic non glycerol (MONG) have a significant effect on the glycerol concentration. So, it is necessary to treat the impurities. The purpose of this study is to know the effect of chloroform to glycerol purification process with acidification method using hydrochloric acid as pretreatment process. This research was begun with acid addition to the glycerol to neutralize the base content and to split the soap content into free fatty acid and salt, that are more easily separated from glycerol. Then the process was continued with extraction by the solvent chloroform using the variable of test volume ratio (v/v) (1:1, 1:1.5, 1:2)  and the extraction time (20, 40, and 60 minutes). The results showed that the more volume of solvent used, gave less extraction time to produce high purity of glycerol. The highest purity produced in this study amounted to 90,9082% is obtained at the ratio of the volume solvent (v/v) 1:1 with extraction time 60 minutes.